2014
DOI: 10.1128/aem.01711-14
|View full text |Cite
|
Sign up to set email alerts
|

Acetoin Synthesis Acquisition Favors Escherichia coli Growth at Low pH

Abstract: Some members of the family Enterobacteriaceae ferment sugars via the mixed-acid fermentation pathway. This yields large amounts of acids, causing strong and sometimes even lethal acidification of the environment. Other family members employ the 2,3-butanediol fermentation pathway, which generates comparatively less acidic and more neutral end products, such as acetoin and 2,3-butanediol. In this work, we equipped Escherichia coli MG1655 with the budAB operon, encoding the acetoin pathway, from Serratia plymuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previously, we introduced the budAB operon from S. plymuthica RVH1, encoding the α-ALS and α-ALD of the acetoin synthesis pathway, in E. coli MG1655 and observed that this attenuated lethal medium acidification during fermentative growth on glucose ( Vivijs et al, 2014a ). Here, we extended this experiment to S. Typhimurium, S. Enteritidis, and S. flexneri by introducing the pTrc99A-P trc - budAB plasmid into these organisms to see whether other mixed-acid fermenters would show a similar behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we introduced the budAB operon from S. plymuthica RVH1, encoding the α-ALS and α-ALD of the acetoin synthesis pathway, in E. coli MG1655 and observed that this attenuated lethal medium acidification during fermentative growth on glucose ( Vivijs et al, 2014a ). Here, we extended this experiment to S. Typhimurium, S. Enteritidis, and S. flexneri by introducing the pTrc99A-P trc - budAB plasmid into these organisms to see whether other mixed-acid fermenters would show a similar behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In Serratia plymuthica RVH1, a strain previously isolated from a food processing environment ( Van Houdt et al, 2005 ), α-ALS and α-ALD are encoded by the budB and budA genes, respectively, which are located on the budAB operon ( Moons et al, 2011 ). We previously showed that transfer of the S. plymuthica RVH1 budAB operon conveys to Escherichia coli the capacity to produce acetoin, to prevent lethal medium acidification and to reverse acidification ( Vivijs et al, 2014a ). In the present study, we transferred the budAB operon to some additional mixed-acid fermenting enterobacteria, Salmonella Typhimurium, Salmonella Enteritidis, and Shigella flexneri , and show that these also acquire the capacity to produce acetoin.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of acetoin by Escherichia coli strains in vegetables and fruits due to acquisition of buidAB gene alter the normal functionality of Escherichia coli. These two phenomena leads to misdiagnosis of E. coli (7,17).…”
Section: Discussionmentioning
confidence: 99%
“…The compound acetoin (3-hydroxy-2-butanone, AC) is an indispensable flavor enhancer widely applied in foods, cosmetics and chemical synthesis ( Li et al, 2018 ; Xiao et al, 2018 ) and also plays a pivotal role in TMP synthesis as a precursor ( Demain et al, 1967 ; Xiao et al, 2014 ; Peng et al, 2020a ; Zhong et al, 2020a ). To improve the AC accumulation in microbial fermentation, various strategies have been employed, including screening of efficient natural producers of acetoin ( Xiao et al, 2006 ; Zhu et al, 2010 ; Zhang et al, 2011 ; Yin et al, 2018 ; Zhong et al, 2020b ), metabolic engineering ( Vivijs et al, 2014 ; Xu et al, 2015 ; Jang et al, 2017 ; Li et al, 2018 ; Bae et al, 2021 ) and fermentation optimization ( Xiao et al, 2007 ; Zhu and Xu 2010a ; Zhang et al, 2012 ; Yuan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%